Health Disparities Among Transgender Adults in South Korea. (March 2020) - Lee, Hyemin; Operario, Don; van den Berg, Jacob J.; Yi, Horim; Choo, Sungsub; Kim, Seung-Sup
This study aims to identify health disparities among transgender adults in South Korea (hereafter Korea), where they widely experience social stigma. We assessed prevalence of nine health indicators using a nationwide cross-sectional survey of 255 Korean transgender adults in 2017. Standardized prevalence ratios of these indicators were estimated using four nationally representative surveys in Korea that included the same health measures. Overall, transgender adults had a significantly higher risk of adverse health outcomes than the general population in Korea. Specifically, disparities in mental health outcomes between transgender adults and the general population were statistically significant. The prevalence of depressive symptoms was 6.44 and 9.71 times higher among transgender adults than women and men in the general population, respectively. For suicidal ideation, transgender adults reported 6.49 and 18.83 times greater risk than women and men in the general population, respectively. Our findings indicate that Korean transgender adults are at a higher risk of negative health outcomes than the general population.